Analisis Pemikiran Khalid Basalamah Mengenai Kepemimpinan Islam dengan Merujuk Ceramah-Ceramahnya di Media Youtube - Noor, Novia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The presence of leaders is essential for a country or a community to keep peace from order in society. The Qur 'an has many scriptures that discuss leadership and its characteristics. This suggests that leadership characteristics are important to be met as a leader. But now there are many differences in understanding the concept of how to be a good leader, resulting in disunity between societies. In this case, researchers are trying to find out how the concept of islamic leadership is in the perspective of Khalid Basalamah. The study uses a qualitative method to approach interviews with the person and analyze his videos about islamic leadership in youtube. To be the ideal leader there should be seven ideal leaders' criteria of being equitable, firm, forgiving, charitable, possessing vast learning, being physically and spiritually healthy, and courageously defending truth